Fiduciary account – an underestimated form of commercial trading security - Guziński, Wojciech (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
In this article the author presents the matter of fiduciary account functioning in the Polish legal system. In the introduction there is the definition of a bank account in the broader sense and its kinds in accordance with banking law and later the author moves on to a detailed description of the fiduciary account. The consideration concerns security due to a bank account under the banking law and the application of the fiduciary account in Polish law. The author also presents conclusions de lege ferenda in the described matter.